Estudo da formação de micelas e microemulsões contendo nifedipina : influência das fases na estrutura dos sistemas - Oliveira, Dayane Xavier de (2014)
Micelles (MIs) and microemulsions (MEs) are classified as stabilized systems by surfactants and are very similar with respect to their structure and physico-chemical properties. As for the applicability, they have been deployed by being able to carry drugs which have a limited systemic bioavailability by oral route. The formation of these systems is mainly dependent on the types of components used, making it important to study its influence on the structure. The goal of this study was to obtain and characterize micellar and microemulsion systems (containing essential oil of Citrus sinensis (L.) Osbeck as oil phase) stabilized by a nonionic surfactant (Tween 80) and short-chain cosurfactant (alcohol ethyl) which may be used as a delivery system for nifedipine (NFD a model drug) seeking to verify the influence of the phases and the interaction of the drug in the structure of these systems. Ternary and pseudoternary phase diagrams for MIs and MEs, respectively, and were obtained from the formation regions, formulations were selected for physico-chemical characterization and incorporation of NFD. The macro and microscopic aspects were evaluated using polarized light microscopy (MLP), measures pH, electrical conductivity and surface tension. The average droplet size was measured by dynamic light scattering (DLS) and small angle x-ray scattering (SAXS). The results demonstrated that such systems are stable, optically isotropic and transparent in the absence and presence of drug. The droplet size decreases with increasing amount of surfactant to MIs and the mixture surfactant/cosurfactant to the MEs. The influence of the cosurfactant in MIs was negligible. The increase of the amount of oily phase in MEs caused an increase in the droplet size. The presence of NFD no influence on the structure of MIs, but for the MEs increased droplet size, suggesting that the NFD is the internal phase of the MEs. The modeling by SAXS curves for MIs and MEs most diluted were made and showed the interaction between the NFD and systems, confirming the previous results. Studies by Fourier Transformed Infra Red (FTIR) confirmed the interaction between MIs and MEs with the stratum corneum (EC) , which allows the use of these systems as permeation enhancers of NFD.